Computer-assisted instruction to Index to Philippine Periodicals - Lumague, Blythe M. (1999)
The main concern of this study is to create an alternative tool to render an end-user database national instructions. The program developed through the use of MS Office Power Point (Windows 97). It takes 16 minutes to view the five modules plus the introduction. The CASI is created following four useful steps: stating the objectives, designing the presentation, writing the program, testing and revising the program.